1974
DOI: 10.1530/acta.0.0770266
|View full text |Cite
|
Sign up to set email alerts
|

RELATION OF TSH CONCENTRATION IN BLOOD TO THE RADIOACTIVE RUBIDIUM 86Rb UPTAKE IN THE THYROID GLAND OF RATS: EVIDENCE OF TSH REGULATORY EFFECT ON THYROID GLAND BLOOD FLOW

Abstract: To study the relations between thyroid gland blood flow and the concentration of thyroid-stimulating hormone (TSH) in rats, a graded concentration of endogenous TSH was induced: for a period of 10 days, methylthiouracil was added to the food (Alkiron, Spofa, 0.2%) and in addition, in the respective groups, dried thyroid gland preparation (Thyreoidin, Spofa) in concentrations of 0.01, 0.02, 0.03, 0.04 and 0.05%. The concentration of TSH was estimated by means of the McKenzie bioassay (results are given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Close correlation has been shown between TBF and serum TSH concentra¬ tions in rats after 10 days' methimazole administra¬ tion (Kapitola et al 1974). In contrast, we found no correlation between TSH and TBF response.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Close correlation has been shown between TBF and serum TSH concentra¬ tions in rats after 10 days' methimazole administra¬ tion (Kapitola et al 1974). In contrast, we found no correlation between TSH and TBF response.…”
Section: Discussionmentioning
confidence: 94%
“…Some investigators have shown a stimulatory effect of bovine TSH on TBF (Söderberg 1958;Solomon et al 1963;Clayton & Szego 1967;Varga et al 1971;Kapitola et al 1974), whereas others (Rosenberg et al 1965;Dumont 1971;Rocmans et al 1978) have observed no significant changes in TBF; decreased TBF values have also been re¬ ported (Goldsmith et al 1965;Ahn et al 1969). These studies used less appropriate techniques for blood flow measurement, however, as pointed out previously (Söderberg 1959).…”
mentioning
confidence: 99%
“…After cessation of antithyroid medications, the patient was rendered euthyroid and the symptoms of TIA ceased [ 1 ]. In this case, it was theorized that the increased thyroid blood flow was stimulated by the high levels of TSH (>100 mIU/ml) [ 1 , 4 ]. The other three documented cases of TSS were all in patients who presented with recurrent TIAs and were found to have a voluminous thyroid goiter [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…TSH-induced alterations in the metabolic activity and structure of the thyroid gland may be accompanied by alterations in thyroid blood flow (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We reported recently (1) that the vascular C/mass (and blood flow) of the thyroid gland is decreased at very low plasma TSH levels and increased at very high plasma TSH levels, but is unchanged over a broad intermediate range of plasma TSH, encompassing normal.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid blood flow per mass of tissue is decreased 6 (1) or 30 (9) days after hypophysectomy, while replacement with bovine TSH can normalize thyroid blood flow (1). Chronic treatment with thioamides, which induce hypothyroidism and elevate endogenous plasma TSH levels, results in increased thyroid blood flow (1,(10)(11)(12). We reported recently (1) that thyroid vascular conductance (C) or blood flow per mass of gland is increased only at very high levels of plasma TSH.…”
mentioning
confidence: 99%